The Temple Management System for Social - จีรภัทร์ บุญเลิศ; ศิริวรรณ อินถา; ศรีวิชัย สุทธิพงษ์; ฐิตสาโร พระมหาสหัส; จีรภัทร์ นิภา (Journal of Educational Review Faculty of Education in MCU, 2018)
The research on the temple management system for society was a survey research with intention to study the current temple management sytem, to study the temple development system and the temple management system, and to study the temple management system and social problem solution. The populations of this study were abbots, monks, novices, and people making merit at the temples in Bangkok and surrounding areas. The samples were 800 monks, novices and lay-people. The samples were obtained by Taro Yamane formula n = 1 N(e) 2 N  Statistics used to analyze the data were frequency, percentage, mean, standard deviation, t-test and F-test. The results showed the temple management system for society in the opinion of the public was at a high level, but in a moderate level in the monks’ opinion. This indicated that the temple management system must be improved urgently. The temple management system and the temple development system were at a moderate level. The Sangha’s organization management, temple management planning, temple activities, function, method and duty in work, temple management and social problem solution, and ability in problem solving were at a high level. Any way, the temple management system for society should be improved in every aspect in order to serve the need of society.